(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
To maintain competitiveness and gain a competitive advantage in the market of educational services for higher education institutions it has become a priority to effectively address and adequately respond to developments and changes in the external environment. In the presented situation, the RA higher education institutions must identify potential risks to the competitiveness and performance effectiveness of the organization, analyze the environmental risk factors influencing the effectiveness of strategic management system, and implement effective risk management. In order to manage these risks HEIs need to develop a comprehensive strategy and action plan to address the risks, as well as monitor and control the results to improve the process. In this context, higher education institutions should integrate risk management into the functions of strategic management as the most important and key component of it. The aim of the article is to identify the necessity of risk management in the strategic management process of the higher education institutions of RA as a premise for ensuring efficiency of statutory activities and strategy. The novelty of the research is the definitions and provisions of risk management proposed in this article, which can be of theoretical and practical value for the Armenian professional literature, taking into account the fact that risk management of HEIs is not developed in the context of RA HEIs. The research methods are the study of professional literature and interrelated factor analysis.